(untitled) (International Journal of Medicine and Medical Sciences, 2011)
Neurilemmoma or schwannoma is a benign, slow growing and encapsulated tumour originating from Schwann cells. Neurilemmoma in the oral cavity are rather uncommon and merits to be differentiated from neurofibroma. We here present a case of neurilemmoma in the floor of mouth with typical histopathological appearance.